Solve the following equation 3(4
– 6e) = 4(8 + 3e)
Solution
Given the equation 3(4 – 6e) = 4(8
+ 3e)
The first step here is to remove brackets (ie open the brackets). We do
this as follows
3(4
– 6e) = 4(8 + 3e)
3*4
– 3*6e = 4*8 + 4*3e
This gives
12 –
18e = 32 + 12e
The like terms have been painted for easy identification
Thus, next is to bring like terms together as follows
12 –
32 = 12e + 18e, which gives
-20
= 30e
Coefficient of e is 30. We now divide both sides by 30 to get
the value of e as follows
-20/30 = 30e/30
and this becomes
-2/3 = e
e = -2/3
Check for correctness
The given equation is 3(4 – 6e) = 4(8 + 3e)
LHS = 3(4 – 6e)
= 3(4
– 6*(-2/3))
= 3(4 + 4)
= 3 * 8
= 24
RHS = 4(8 + 3e)
= 4(8 + 3*(-2/3))
= 4(8 - 2)
= 4*6
= 24
(Same as LHS)
Comments
Post a Comment